+0  
 
0
112
2
avatar

If \(\displaystyle{f(x)=x^{(x+1)}(x+2)^{(x+3)}},\) then find the value of \(f(0)+f(-1)+f(-2)+f(-3)\).

 Oct 31, 2019
 #1
avatar+107095 
+1

Just sub in the numbers and then do the addition.

 

I will start you off

\(\displaystyle{f(x)=x^{(x+1)}(x+2)^{(x+3)}}\\ \displaystyle{f(0)=0^{(0+1)}(0+2)^{(0+3)}}\\ \displaystyle{f(0)=0^{1}*2^3}\\ \displaystyle{f(0)=0}\)

.
 Oct 31, 2019
edited by Melody  Oct 31, 2019
 #2
avatar+308 
+3

Notice that Guest used the word asap in his title. This is one of the things that most answerers don't like.

 Oct 31, 2019

39 Online Users

avatar